Home My Page Projects Code Snippets Project Openings diderot
Summary Activity Tracker Tasks SCM

SCM Repository

[diderot] Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml
ViewVC logotype

Diff of /branches/charisee_dev/src/compiler/high-il/normalize-ein.sml

Parent Directory Parent Directory | Revision Log Revision Log | View Patch Patch

revision 2450, Thu Oct 3 20:17:08 2013 UTC revision 2458, Tue Oct 8 19:42:58 2013 UTC
# Line 4  Line 4 
4      local      local
5    
6      structure E = Ein      structure E = Ein
7    (* structure P=Printer*)      structure P=Printer
8        structure O =OrderEin
9      in      in
10    
11    
# Line 29  Line 29 
29                  (* end case *)                  (* end case *)
30       end       end
31    
32  (*  
33  fun mkProd [e]=(1,e)  fun mkProd [e]=(1,e)
34      | mkProd(e)=let      | mkProd(e)=let
35      fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')      fun flatten(i,((E.Prod l)::l'))= flatten(1,l@l')
36          |flatten(i,((E.Const c):: l'))=          |flatten(i,((E.Const c):: l'))=
37             if(c>0.0 orelse c<0.0) then                  if(c>0.0 orelse  0.0>c) then (3,[E.Const 0.0])
38                 if (c>1.0 orelse c<1.0) then let                  else flatten(i,l')
                 val(b,a)=flatten(i,l') in (b,[E.Const c]@a) end  
                else flatten(1,l')  
             else (3, [E.Const(0.0)])  
39           | flatten(i,[])=(i,[])           | flatten(i,[])=(i,[])
40           | flatten (i,e::l') =  let           | flatten (i,e::l') =  let val(a,b)=flatten(i,l') in (a,[e]@b) end
41                      val(b,a)=flatten(i,l') in (b,[e]@a) end       val (change,a)=flatten(0,e)
42       val ( b,a)=flatten(0,e)       in if(change=3) then (1,E.Const(0.0))
      in if(b=3) then (1,E.Const(0.0))  
43          else case a          else case a
44          of [] => (1,E.Const(0.0))          of [] => (1,E.Const(0.0))
45          | [e] => (1,e)          | [e] => (1,e)
46          | es => (b, E.Prod es)          | es => (change, E.Prod es)
47          (* end case *)          (* end case *)
48           end           end
49    
50    (*
51    
52  fun mkEps(e)= (case e  fun mkEps(e)= (case e
53      of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)      of E.Apply(E.Partial [E.V a], E.Prod( e2::m ))=> (0,e)
# Line 65  Line 62 
62      |_=> (0,e)      |_=> (0,e)
63      (*end case*))      (*end case*))
64    
65  fun mkApply(E.Apply(d, e)) = (case e  
     of E.Tensor(a,[])=> (0,E.Const(0.0))  
      | E.Tensor _=> (0,E.Apply(d,e))  
      | E.Const _=> (1,E.Const(0.0))  
      | E.Add l => (1,E.Add(List.map (fn e => E.Apply(d, e)) l))  
      | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(d, e2), E.Apply(d, e3)))  
      | E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))  
      | E.Prod[E.Tensor(a,[]), e2]=>  (0, E.Prod[ E.Tensor(a,[]), E.Apply(d, e2)]  )  
      | E.Prod((E.Tensor(a,[]))::e2)=>  (0, E.Prod[E.Tensor(a,[]), E.Apply(d, E.Prod e2)] )  
      | E.Prod es =>    (let  
            fun prod [e] = (E.Apply(d, e))  
               | prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]  
                    val lr=e2 @[E.Apply(d,e1)]   val(b,a) =mkProd lr  
                 in ( E.Add[ a, m] )  
                 end)  
              | prod _= (E.Const(1.0))  
                 in (1,prod es)  
                 end)  
              | _=> (0,E.Apply(d,e))  
              (*end case*))  
66    
67  fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e  fun mkSumApply(E.Sum(c,E.Apply(d, e))) = (case e
68      of E.Tensor(a,[])=> (0,E.Const(0.0))      of E.Tensor(a,[])=> (0,E.Const(0.0))
# Line 94  Line 72 
72      | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(d, e))) l))      | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(d, e))) l))
73      | E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(d, e2)), E.Sum(c,E.Apply(d, e3))))      | E.Sub(e2, e3) =>(1, E.Sub(E.Sum(c,E.Apply(d, e2)), E.Sum(c,E.Apply(d, e3))))
74      | E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))      | E.Prod((E.Epsilon c)::e2)=> mkEps(E.Apply(d,e))
75      | E.Prod[E.Tensor(a,[]), e2]=>  (0, E.Prod[ E.Tensor(a,[]), E.Sum(c,E.Apply(d, e2))]  )      | E.Prod[E.Tensor(a,[]), e2]=>  (1, E.Prod[ E.Tensor(a,[]), E.Sum(c,E.Apply(d, e2))]  )
76      | E.Prod((E.Tensor(a,[]))::e2)=>  (0, E.Prod[E.Tensor(a,[]), E.Sum(c,E.Apply(d, E.Prod e2))] )      | E.Prod((E.Tensor(a,[]))::e2)=>  (1, E.Prod[E.Tensor(a,[]), E.Sum(c,E.Apply(d, E.Prod e2))] )
77      | E.Prod es =>   (let      | E.Prod es =>   (let
78          fun prod [e] = (E.Apply(d, e))          fun prod [e] = (E.Apply(d, e))
79          | prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]          | prod(e1::e2)=(let val l= prod(e2) val m= E.Prod[e1,l]
# Line 106  Line 84 
84      | _=> (0,E.Sum(c,E.Apply(d,e)))      | _=> (0,E.Sum(c,E.Apply(d,e)))
85      (*end case*))      (*end case*))
86    
   
   
 (* Identity: (Epsilon ijk Epsilon ilm) e => (Delta jl Delta km - Delta jm Delta kl) e  
     The epsToDels Function searches for Epsilons in the expression, checks for this identity in all adjacent Epsilons and if needed, does the transformation.  
      The Function returns two separate list, 1 is the remaining list of Epsilons that have not be changed to deltas, and the second is the Product of the remaining expression.  
   Ex:(Epsilon_ijk Epsilon_ilm) Epsilon_stu e =>([Epsilon_stu], [Delta_jl,Delta_km,e -Delta_jm Delta_kl, e] )  
    This is useful since we can normalize the second list without having to normalize the epsilons again.  
         4(Eps Eps)  
        3( Delta_liDelta mj- Delta_mi Delta_lj)  
          Ai-  
87          *)          *)
88    
89    
90                     *)  fun rmEpsIndex(_,_,[])=[]
91    | rmEpsIndex([],[],cs)=cs
92    | rmEpsIndex([],m ,e1::cs)=[e1]@rmEpsIndex(m,[],cs)
93    | rmEpsIndex(i::ix,rest ,(E.V c)::cs)=
94        if(i=c) then rmEpsIndex(rest@ix,[],cs)
95        else rmEpsIndex(ix,rest@[i],(E.V c)::cs)
96    
97    
98    (* Transform eps to deltas*)
99  fun epsToDels(E.Sum(count,E.Prod e))= let  fun epsToDels(E.Sum(count,E.Prod e))= let
100      fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=      fun doubleEps((E.Epsilon (a,b,c))::(E.Epsilon(d,e,f))::es,eps,e3)=
101          let          let
# Line 132  Line 106 
106              (*remove index from original index list*)              (*remove index from original index list*)
107              (*currrent, left, sumIndex*)              (*currrent, left, sumIndex*)
108    
109              fun rmIndex(_,_,[])=[]              val s'= rmEpsIndex([i,s,t,u,v],[],count)
             | rmIndex([],[],cs)=cs  
             | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)  
             | rmIndex(i::ix,rest ,(E.V c)::cs)=  
                    if(i=c) then rmIndex(rest@ix,[],cs)  
                    else rmIndex(ix,rest@[i],(E.V c)::cs)  
   
             val s'= rmIndex([i,s,t,u,v],[],count)  
110              val s''=[E.V s, E.V t ,E.V u, E.V v]              val s''=[E.V s, E.V t ,E.V u, E.V v]
111              val deltas= E.Sub(              val deltas= E.Sub(
112                      E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),                      E.Sum(s'',E.Prod([E.Delta(E.V s,E.V u), E.Delta(E.V t,E.V v)] @e3)),
# Line 177  Line 144 
144              |_=> dist(current, eps@[c1],rest))              |_=> dist(current, eps@[c1],rest))
145          end          end
146    
   
   
147      val (es,rest)=findeps([],e)      val (es,rest)=findeps([],e)
148    
149      in      in
150          dist(es,[],rest)          dist(es,[],rest)
151      end      end
152    
 (*  
   
   
   
   
 (*The Deltas then need to be distributed over to the tensors in the expression e.  
 Ex.:Delta ij ,Tensor_j, e=> Tensor_i,e. The mkDelts function compares every Delta in the expression to the tensors in the expressions while keeping the results in the correct order.  
    This also returns a list of deltas and a list of the remaining expression.  
   *)  
   
 fun mkDel(e) = let  
     fun Del(i, [],x)= (i,[],x)  
        | Del(i, d,[])=(i, d,[])  
        | Del(i, (E.Delta(d1,d2))::d, (E.Tensor(id,[x]))::xs)=  
             if(x=d2) then (let  
                val(i',s,t)= Del(i+1,d, xs)  
                in Del(i',s, [E.Tensor(id, [d1])] @t) end)  
             else (let val (i',s,t)= Del(i,[E.Delta(d1,d2)],xs)  
                val(i2,s2,t2)= Del(i',d,[E.Tensor(id,[x])]@t)  
                in (i2,s@s2, t2) end )  
        | Del(i, (E.Delta(d1,d2))::d, (E.Field(id,[x]))::xs)=  
                    if(x=d2) then (let  
                    val(i',s,t)= Del(i+1,d, xs)  
                    in Del(i',s, [E.Field(id, [d1])] @t) end)  
                    else (let val (i',s,t)= Del(i,[E.Delta(d1,d2)],xs)  
                    val(i2,s2,t2)= Del(i',d,[E.Field(id,[x])]@t)  
                    in (i2,s@s2, t2) end )  
   
         | Del(i, d, t)= (i,d,t)  
     fun findels(e,[])= (e,[])  
        | findels(e,es)= let val del1= hd(es)  
             in (case del1  
                of E.Delta _=> findels(e@[del1],tl(es))  
                 |_=> (e, es))  
             end  
     val(a,b)= findels([], e)  
     in  
       Del(0, a, b)  
     end  
153    
154    fun rmIndex(_,_,[])=[]
155        | rmIndex([],[],cs)=cs
156        | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)
157        | rmIndex(i::ix,rest ,c::cs)=
158            if(i=c) then rmIndex(rest@ix,[],cs)
159            else rmIndex(ix,rest@[i],c::cs)
160    
161  (*The Deltas are distributed over to the tensors in the expression e.  (* Apply deltas to tensors/fields*)
  This function checks for instances of the dotProduct.  
 Sum_2 (Delta_ij (A_i B_j D_k))=>Sum_1(A_i B_i) D_k  
 *)  
    fun checkDot(E.Sum(s,E.Prod e))= let  
        fun dot(i,d,r, (E.Tensor(ida,[a]))::(E.Tensor(idb,[b]))::ts)=  
                    if (a=b) then  
                         dot(i-1,d@[E.Sum(1,E.Prod[(E.Tensor(ida,[a])), (E.Tensor(idb,[b]))])], [],r@ts)  
                    else dot(i,d, r@[E.Tensor(idb,[b])],(E.Tensor(ida,[a]))::ts)  
           |dot(i, d,r, [t])=dot(i,d@[t], [], r)  
           |dot(i,d, [],[])= (i,d, [],[])  
           |dot(i,d, r, [])= dot(i,d, [], r)  
           |dot(i, d, r, (E.Prod p)::t)= dot (i, d, r, p@t)  
           |dot(i,d, r, e)= (i,d@r@e, [], [])  
   
         val(i,d,r,c)= dot(s,[],[], e)  
         val soln= (case d of [d1]=>d1  
                    |_=> E.Prod d)  
         in E.Sum(i,soln) end  
       |checkDot(e)= (e)  
   
   
   
   
   
   
                 *)  
   
162  fun reduceDelta(E.Sum(c,E.Prod p))=let  fun reduceDelta(E.Sum(c,E.Prod p))=let
163    
164      fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)      fun findDeltas(dels,rest,E.Delta d::es)= findDeltas(dels@[E.Delta d], rest, es)
165      | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)      | findDeltas(dels,rest,E.Epsilon eps::es)=findDeltas(dels,rest@[E.Epsilon eps],es)
166      | findDeltas(dels,rest,es)=  (dels,rest,es)      | findDeltas(dels,rest,es)=  (dels,rest,es)
167    
     fun rmIndex(_,_,[])=[]  
         | rmIndex([],[],cs)=cs  
         | rmIndex([],m ,e1::cs)=[e1]@rmIndex(m,[],cs)  
         | rmIndex(i::ix,rest ,c::cs)=  
             if(i=c) then rmIndex(rest@ix,[],cs)  
             else rmIndex(ix,rest@[i],c::cs)  
168    
169      fun distribute(change,d,dels,[],done)=(change,dels@d,done)      fun distribute(change,d,dels,[],done)=(change,dels@d,done)
170          | distribute(change,[],[],e,done)=(change,[],done@e)          | distribute(change,[],[],e,done)=(change,[],done@e)
171          | distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=          | distribute(change,E.Delta(i,j)::ds,dels,E.Tensor(id,[tx])::es,done)=
172              if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])              if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Tensor(id,[i])])
173              else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)              else distribute(change,ds,dels@[E.Delta(i,j)],E.Tensor(id,[tx])::es,done)
174        | distribute(change,E.Delta(i,j)::ds,dels,E.Field(id,[tx])::es,done)=
175            if(j=tx) then distribute(change@[j],dels@ds,[] ,es ,done@[E.Field(id,[i])])
176            else distribute(change,ds,dels@[E.Delta(i,j)],E.Field(id,[tx])::es,done)
177          | distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])          | distribute(change,d,dels,e::es,done)=distribute(change,dels@d,[],es,done@[e])
178    
179      val (dels,eps,es)=findDeltas([],[],p)      val (dels,eps,es)=findDeltas([],[],p)
# Line 283  Line 185 
185    end    end
186    
187    
188    fun mkApplySum(E.Apply(E.Partial d,E.Sum(c,e)))=(print "apply sum";case e
189        of E.Tensor(a,[])=>(1,E.Const 0.0)
190        | E.Const _ =>(1,E.Const 0.0)
191        | E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, E.Sum(c,e))) l))
192        | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, E.Sum(c,e2)), E.Apply(E.Partial d, E.Sum(c,e3))))
193    
194        | E.Prod [e1]=>(1,E.Apply(E.Partial d,E.Sum(c,e1)))
195        | E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,e1))])
196    
197        | E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Sum(c,E.Prod e2))])
198      (*  | E.Prod es=> (let
199            fun prod [e1] =E.Apply(E.Partial d,e1)
200            | prod(e1::e2)=(let
201                val l= prod(e2) val m= E.Prod[e1,l]
202                val lr=e2 @[E.Apply(E.Partial d,e1)] val(b,a) =mkProd lr
203                in  E.Add[a,m]
204                end)
205            in (1,prod es) end)*)
206        |_=>(0,E.Apply(E.Partial d,E.Sum(c,e)))
207        (* end case*))
208    
209    fun mkApply2(E.Apply(E.Partial d,e))=(print "aa";case e
210        of E.Tensor(a,[])=>(1,E.Const 0.0)
211        | E.Const _ =>(1,E.Const 0.0)
212        | E.Add l => (1,E.Add(List.map (fn e => E.Apply(E.Partial d, e)) l))
213        | E.Sub(e2, e3) =>(1, E.Sub(E.Apply(E.Partial d, e2), E.Apply(E.Partial d, e3)))
214        | E.Apply(E.Partial e1,e2)=>(1,E.Apply(E.Partial(d@e1), e2))
215        | E.Prod [e1]=>(1,E.Apply(E.Partial d,e1))
216        | E.Prod(E.Tensor(a,[])::e1::[])=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,e1)])
217        | E.Prod(E.Tensor(a,[])::e2)=>(1,E.Prod[E.Tensor(a,[]),E.Apply(E.Partial d,E.Prod e2)])
218        | E.Prod es=> (let
219            fun prod [e1] =(0,E.Apply(E.Partial d,e1))
220    
221            | prod(E.Tensor t::e2)=(let
222                val (change,l)= prod(e2) val m= E.Prod[E.Tensor t,l]
223                val lr=e2 @[E.Apply(E.Partial d,E.Tensor t)] val(b,a) =mkProd lr
224                in  (1,E.Add[a,m])
225                end)
226            | prod(E.Field f::e2)=(let
227                val (change,l)= prod(e2) val m= E.Prod[E.Field f,l]
228                val lr=e2 @[E.Apply(E.Partial d,E.Field f)] val(b,a) =mkProd lr
229                in  (1,E.Add[a,m])
230                end)
231            | prod e = (0,E.Apply(E.Partial d, E.Prod e))
232                    (*)prod (e1::e2)= E.Apply(E.Partial d, E.Prod ([e1]@e2))
233    *)
234    
235            val (a,b)= prod es
236    
237            in (a, b) end)
238        |_=>(0,E.Apply(E.Partial d,e))
239        (* end case*))
240    
241    fun mkSumApply2(E.Sum(c,E.Apply(E.Partial d,e)))=(print "in here ";case e
242        of E.Const _=>(1,E.Const 0.0)
243        | E.Tensor(_,[])=> (1,E.Const 0.0)
244        | E.Field _=>(0,E.Sum(c,E.Apply(E.Partial d,e)))
245        | E.Apply(E.Partial e1,e2)=>(1,E.Sum(c,E.Apply(E.Partial(d@e1),e2)))
246    
247        | E.Add l => (1,E.Add(List.map (fn e => E.Sum(c,E.Apply(E.Partial d, e))) l))
248        | E.Sub(e2, e3) =>
249                    (*(0,E.Sub(e2,e3))
250                    *)
251                    (print "sub";(1, E.Sub(E.Sum(c,E.Apply(E.Partial d, e2)), E.Sum(c,E.Apply(E.Partial d, e3)))))
252    
253         | E.Prod [e1]=>(print "one";(1,E.Sum(c,E.Apply(E.Partial d,e1))))
254    
255    
256        | E.Prod(E.Tensor(a,[])::e2::[])=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,e2))]))
257    
258        | E.Prod(E.Tensor(a,[])::e2)=>("in scalar";(1, E.Prod[E.Tensor(a,[]),E.Sum(c,E.Apply(E.Partial d,E.Prod e2))]))
259    
260        | E.Prod es =>(print "in prod";let
261            fun prod (change,rest, sum,partial,[]) = (change,E.Sum(sum,E.Apply(E.Partial partial,E.Prod rest)))
262            | prod (change,rest, sum,partial,E.Epsilon(i,j,k)::ps)= let
263                fun matchprod(2,_,_,_)= 1 (*matched 2*)
264                | matchprod(num,_,_,[])=0
265                | matchprod(0,_,_,[eps])=0
266                | matchprod(num,[],rest,eps::epsx)=
267                    matchprod(num,rest,[],epsx)
268                | matchprod(num,E.V p::px,rest,eps::epsx)=
269                    if(p=eps) then matchprod(num+1,px,rest,epsx)
270                    else matchprod(num,px,rest@[E.V p], eps::epsx)
271                | matchprod(num,p::px,rest,eps)=
272                    matchprod(num,px,rest,eps)
273    
274                val change'= matchprod(0,d,[],[i,j,k])
275                in (case change'
276                    of 1 => (1,E.Const 0.0)
277                    | _ =>prod(change,rest@[E.Epsilon(i,j,k)],sum,partial,ps)
278                    (*end case*))
279                end
280            | prod (change,rest, sum,partial,E.Delta(i,j)::ps)=let
281                fun applyDelPartial([],_)=(0,[])
282                | applyDelPartial(p::px,r)=
283                    if(j=p) then (1,r@[i]@px)
284                    else  applyDelPartial(px,r@[p])
285    
286                val (change',px)=applyDelPartial(d,[])
287    
288                in (case change'
289                    of 1 => (let val index=rmIndex([j],[],sum)
290                        in prod(1,rest, index,px, ps) end )
291                    | _ => prod(change,rest@[E.Delta(i,j)], sum,partial, ps)
292                    (*end case*)) end
293    
294            | prod (change,rest,sum, partial,e::es)= prod(change,rest@[e],sum,partial,es)
295    
296            val (change,exp) = prod(0,[],c, d, es)
297    
298            in
299                (change,exp)
300            end)
301            | _=>(print "nope";(0,E.Sum(c,E.Apply(E.Partial d,e))))
302            (* end case*))
303    
304    (*
305    E.Sum(c,Apply(d,e))
306        try E.Sum(c,e)=> E.Sum(c',e')
307        ==>    E.Sum(c',E.Apply(d,e'))
308            E.Apply(d,e')=> E.Apply(d',e'')
309        ==>E.Sum(c',E.Apply(d',e'')
310    *)
311    
312  (*Apply normalize to each term in product list  (*Apply normalize to each term in product list
313  or Apply normalize to tail of each list*)  or Apply normalize to tail of each list*)
314  fun normalize (Ein.EIN{params, index, body}) = let  fun normalize (Ein.EIN{params, index, body}) = let
315    
316        val changed = ref false        val changed = ref false
317    
318        fun rewriteBody body = (case body        fun rewriteBody body = (case body
319               of E.Const _=> body               of E.Const _=> body
320                | E.Tensor _ =>body                | E.Tensor _ =>body
# Line 298  Line 325 
325                | E.Epsilon _=>body                | E.Epsilon _=>body
326    
327                | E.Neg e => E.Neg(rewriteBody e)                | E.Neg e => E.Neg(rewriteBody e)
328                | E.Add es => let val (b,a)= mkAdd(List.map rewriteBody es)                | E.Add es => let val (change,body')= mkAdd(List.map rewriteBody es)
329                     in if (b=1) then ( changed:=true;a) else a end                     in if (change=1) then ( changed:=true;body') else body' end
330                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)                | E.Sub (a,b)=>  E.Sub(rewriteBody a, rewriteBody b)
331                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)                | E.Div (a, b) => E.Div(rewriteBody a, rewriteBody b)
332                | E.Partial _=>body                | E.Partial _=>body
# Line 316  Line 343 
343                | E.Prod [E.Partial r1,E.Conv(f,deltas)]=>                | E.Prod [E.Partial r1,E.Conv(f,deltas)]=>
344                     (changed :=true;E.Conv(f,deltas@r1))                     (changed :=true;E.Conv(f,deltas@r1))
345                | E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>                | E.Prod (E.Partial r1::E.Conv(f,deltas)::ps)=>
346                     (changed:=true; E.Prod([E.Conv(f,deltas@r1)]@ps))                     (changed:=true;
347                        let val (change,e)=mkProd([E.Conv(f,deltas@r1)]@ps)
348                        in e end)
349                  | E.Prod[(E.Epsilon(e1,e2,e3)), E.Tensor(_,[E.V i1,E.V i2])]=>
350                        if(e2=i1 andalso e3=i2) then (changed :=true;E.Const(0.0))
351                        else body
352                 | E.Prod [E.Partial r1, E.Tensor(_,[])]=> (changed:=true;E.Const(0.0))
353                 | E.Prod(E.Partial r1::E.Partial r2::p)=>
354                       (changed:=true;E.Prod([E.Partial(r1@r2)]@p))
355                 | E.Prod [E.Partial _, _] =>body
356    
357                 | E.Prod (E.Partial p1::es)=> (let
358                    fun prod [e1] =E.Apply(E.Partial p1,e1)
359                    | prod(e1::e2)=(let
360                        val l= prod(e2) val m= E.Prod[e1,l]
361                        val lr=e2 @[E.Apply(E.Partial p1,e1)] val(b,a) =mkProd lr
362                        in  E.Add[a,m]
363                        end)
364                    in (changed:=true;prod es) end)
365    
366                | E.Prod(e::es)=>let                | E.Prod(e::es)=>let
367                      val e'=rewriteBody e                      val e'=rewriteBody e
368                      val e2=rewriteBody(E.Prod es)                      val e2=rewriteBody(E.Prod es)
369                      in(case e2 of E.Prod p'=> E.Prod([e']@p')                      val(a,b)=(case e2 of E.Prod p'=> mkProd([e']@p')
370                          |_=>E.Prod [e',e2])                          |_=>mkProd [e',e2])
371                        in b
372                     end                     end
373    
374                (*Apply*)                (*Apply*)
375    
376                  | E.Apply(E.Partial d,E.Sum(c,e))=>let
377                        val(c,e')=mkApplySum(E.Apply(E.Partial d,E.Sum(c, rewriteBody e)))
378                    in (case c of 1=>(changed:=true;e')
379                        |_=> e')end
380                  | E.Apply(E.Partial [],e)=> e
381    
382                  | E.Apply(E.Partial p, e)=>let
383                        val body'=E.Apply(E.Partial p, rewriteBody e)
384                        val (c, e')=mkApply2(body')
385                    in (case c of 1=>(changed:=true;e')
386                        | _ =>e') end
387                | E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)                | E.Apply(e1,e2)=>E.Apply(rewriteBody e1, rewriteBody e2)
388    
389    
390    
391                (* Sum *)                (* Sum *)
392                | E.Sum([],e)=> rewriteBody e                | E.Sum([],e)=> (changed:=true;rewriteBody e)
393                     | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)                     | E.Sum(_,E.Const c)=>(changed:=true;E.Const c)
394                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))                | E.Sum(c,(E.Add l))=> (changed:=true;E.Add(List.map (fn e => E.Sum(c,e)) l))
395                  | E.Sum(c,E.Sub(e1,e2))=>(changed:=true; E.Sub(E.Sum(c,e1),E.Sum(c,e2)))
396                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>                | E.Sum(c,E.Prod(E.Epsilon eps1::E.Epsilon eps2::ps))=>
397                     let val (i,e,rest)=epsToDels(body)                     let val (i,e,rest)=epsToDels(body)
398                     in (case (i, e,rest)                     in (case (i, e,rest)
# Line 343  Line 401 
401                          |(0,eps,rest)=>(let                          |(0,eps,rest)=>(let
402                              val p'=rewriteBody(E.Prod rest)                              val p'=rewriteBody(E.Prod rest)
403                              val p''= (case p' of E.Prod p=>p |e=>[e])                              val p''= (case p' of E.Prod p=>p |e=>[e])
404                              in E.Sum(c, E.Prod (eps@p'')) end                              val(a,b)= mkProd (eps@p'')
405                                in E.Sum(c,b) end
406                              )                              )
407                          |_=>body                          |_=>body)
408                     ) end                     end
409                | E.Sum(c, E.Prod(E.Delta d::es))=>let                | E.Sum(c, E.Prod(E.Delta d::es))=>let
410                      val (change,body')=reduceDelta(body)                      val (change,a)=reduceDelta(body)
411                        val (change',body')=(case a
412                            of E.Prod p=> mkProd p
413                            |_=> (0,a))
414                     in (case change of []=>body'|_=>(changed:=true;body')) end                     in (case change of []=>body'|_=>(changed:=true;body')) end
415    
416                  | E.Sum(c,E.Apply(E.Partial _,e))=>let
417                        val (change,exp)=mkSumApply2(body)
418                        val exp'=(case exp
419                            of  E.Const c => E.Const c
420                            | E.Sum(c',E.Apply(d',e'))  => (let
421                                val s'=rewriteBody(E.Sum(c',e'))
422                               in (case s'
423                                    of E.Sum([],e'')=>E.Apply(d',e'')
424                                    | E.Sum(s'',e'') => E.Sum(s'',E.Apply(d',e''))
425                                    | _ => E.Apply(d',s'))
426    
427                                end)
428    
429    
430                            | _ =>exp
431                            (* end case *))
432    
433                    in (case change of 1=>(changed:=true;exp') |_=>exp')
434                    end
435    
436    
437                | E.Sum(c,e)=>E.Sum(c,rewriteBody e)                | E.Sum(c,e)=>E.Sum(c,rewriteBody e)
438    
439              (*end case*))              (*end case*))
# Line 358  Line 442 
442              val body' = rewriteBody body              val body' = rewriteBody body
443              in              in
444                if !changed                if !changed
445                     then (changed := false; (*print " \n \t => \n \t ";print( P.printbody body');print "\n";*)loop body')                     then (changed := false; print " \n \t => \n \t ";print( P.printbody body');print "\n";loop body')
446                  else body'                  else (P.printbody(body');body')
447              end              end
448      val b = loop body      val b = loop body
449      in      in

Legend:
Removed from v.2450  
changed lines
  Added in v.2458

root@smlnj-gforge.cs.uchicago.edu
ViewVC Help
Powered by ViewVC 1.0.0